Analytical and Stochastic Modeling Techniques and Applications 20th International Conference, ASMTA 2013, Ghent, Belgium, July 8-10, 2013. Proceedings - Dudin, Alexander; Turck, Koen.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 20th International Conference on Analytical and Stochastic Modelling and Applications, ASMTA 2013, held in Ghent, Belgium, in July 2013. The 32 papers presented were carefully reviewed and selected from numerous submissions. The focus of the papers is on the following application topics: complex systems; computer and information systems; communication systems and networks; wireless and mobile systems and networks; peer-to-peer application and services; embedded systems and sensor networks; workload modelling and characterization; road traffic and transportation; social networks; measurements and hybrid techniques; modeling of virtualization; energy-aware optimization; stochastic modeling for systems biology; biologically inspired network design.
Complex systems -- Computer and information systems -- Communication systems and networks -- Wireless and mobile systems and networks -- Peer-to-peer application and services -- Embedded systems and sensor networks -- Workload modeling and characterization -- Road traffic and transportation -- Social networks -- Measurements and hybrid techniques -- Modeling of virtualization -- Energy-aware optimization -- Stochastic modeling for systems biology -- Biologically inspired network design.
Keywords: Computer science; Computer Communication Networks; Computer system performance; Software engineering; Computer software; Computer Science; Software Engineering; Computer Communication Networks; System Performance and Evaluation; Information Systems Applications (incl. Internet).; Probability and Statistics in Computer Science; Algorithm Analysis and Problem Complexity